Pengenalan Debat Bahasa Inggris Model British Parliamentary Untuk Beginner di Akademi Maritim Nusantara Banjarmasin - Elisa Rosiana; M. Arinal Rahman (BALANTING Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract Debate is an educational method that can make students more critical and able to use arguments well. Not only that, but debate can also increase a student's confidence, especially in foreign languages. Students are expected to become more competent by studying the English debate model. This time, community service was carried out to introduce cadets and cadets at the Banjarmasin Archipelago Maritime Academy (AMNUS) regarding the British Parliamentary debate method. The results of the British Parliamentary model English debate held at AMNUS Banjarmasin as part of this community service program show that the program ran smoothly and achieved its goals. AMNUS Banjarmasin cadets have expressed their interest in an English-language competition in the future and have even discussed the possibility of participating in a debate competition that only uses English. The cadets hope that this introduction and simulated debate will help shape them into independent and well-rounded thinkers. They also claim that the program has helped them become more comfortable debating in English and better understand academic debating conventions. Keywords: Community Service, English for Specific Purposes, British Parliamentary Debate system, Cadets, Maritime English